THE PERCEPTIONS OF CIFS STUDENTS AT WIUT ON THE USAGE OF QUILLBOT IN ACADEMIC WRITING - Jaloliddin Esnaov (International Journal of Literature and Language Studies, 2026)
As the Artificial Intelligence (AI) advances, paraphrasing tool QuillBot becoming more and more popular among students and educators. QuillBot is an innovative tool that supports students by paraphrasing, giving appropriate suggestions, and creating new contents. This research’s main objective is to examine the perceptions of students about usage of QuillBot. Throughout the research quantitative data collection method was utilized, and overall opinions of 41 students were analyzed. The results then were provided. Information about most frequently used features of QuillBot were gathered, and negative and positive effects of them were analyzed. In the report information about limitations were provided, and future recommendations were given.